2011
DOI: 10.1039/c0lc00656d
|View full text |Cite
|
Sign up to set email alerts
|

Cell sorting by endocytotic capacity in a microfluidic magnetophoresis device

Abstract: Magnetically labelled cells are finding a wealth of applications for in vitro analysis as well as in vivo treatments. Sorting of cells into subpopulations based on their magnetite loading is an important step in such procedures. Here, we study the sorting of monocytes and macrophages which internalise nanoparticles to different extents based on their endocytotic capacity. Macrophages featured a high endocytotic activity and were found to internalise between 4 and 60 pg of iron per cell. They were successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(84 citation statements)
references
References 60 publications
(62 reference statements)
0
83
0
1
Order By: Relevance
“…Magnetic cell manipulation that applies to magnetophoresis can also be applied to magnetic cell sorting (Figure 13), where we can separate cells in respect to their magnetic load [38]. This may be particularly advantageous when we want a precise and homogenous iron load within a cell fraction and/or want to eliminate poorly loaded cells that would, for example, be less detectable by MRI or less responsible to magnetic targeting.…”
Section: Magnetic Manipulation Of Cells: From Cell Sorting To Magnetimentioning
confidence: 99%
“…Magnetic cell manipulation that applies to magnetophoresis can also be applied to magnetic cell sorting (Figure 13), where we can separate cells in respect to their magnetic load [38]. This may be particularly advantageous when we want a precise and homogenous iron load within a cell fraction and/or want to eliminate poorly loaded cells that would, for example, be less detectable by MRI or less responsible to magnetic targeting.…”
Section: Magnetic Manipulation Of Cells: From Cell Sorting To Magnetimentioning
confidence: 99%
“…Several groups have also described the use of microfluidic devices to deflect particles across streamlines and into different outlets based on their different magnetic contents. 225,226 In these systems, we observed that bacteria motility is also a challenge.…”
Section: Introductionmentioning
confidence: 97%
“…In the past few years, several microfluidic based magnetic sorting concepts have been investigated to capture magnetic beads or magnetically labeled cells. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, these devices are generally hampered by complex fabrication processes and low volumetric throughputs. In many earlier studies, flow rates were limited to less than 1 ml/h, 9,10 which are not practical for many realworld applications.…”
Section: Introductionmentioning
confidence: 99%